Knowledge and Behavior Regarding Intermittent Fasting - Meity Moga Layuk; Ratih Wirapuspita Wisnuwardani (Mulawarman International Conference on Tropical Public Health, 2025)
Background : Intermittent fasting (IF), often integrated into carbohydrate-restricted diets, has rapidly gained interest among the general public and patients with cardiometabolic disease. However, there are limited studies investigating the relationship between IF knowledge, IF practice and healthy lifestyle behaviors. Objective : The study aimed to determine the association between the level of IF knowledge, Intermittent Fasting practices and healthy lifestyle behaviors among adults in Samarinda, Indonesia. Research Methods/ Implementation Methods : This study employed a cross-sectional design, involving 129 respondents recruited through an online questionnaire. Data collected included demographic characteristics, IF knowledge, Intermittent Fasting practices, and healthy lifestyle behaviors (covering diet, physical activity, sleep duration, non-alcoholic consumption, non-smoking, and stress management). Data analysis utilized the Chi-Square test to assess the association between respondent characteristics and IF practices, and the Spearman correlation test to analyze the association between IF knowledge and healthy lifestyle behaviors. Results : There was no significant difference found between most respondent characteristics and IF practices, except for having received IF information (p<0.0001). A significant association was observed between IF knowledge and IF practices ((p<0.0001). However, there was no association between IF knowledge and overall healthy lifestyle behaviors, including dietary patterns (p=0.249). Conclusion/Lesson Learned : Higher IF knowledge is significantly associated with IF practices, but not associated with overall healthy lifestyle behaviors. These findings emphasize the importance of strengthening evidence-based health education to improve public understanding of healthy lifestyle components as an effort toward developing quality human resources. An integrated health promotion strategy that combines knowledge dissemination with practical behavioral support is recommended to enhance community well-being.